THE EFFECT OF FINANCIAL LITERACY AND THE USE OF CORETAX ON PERCEPTIONS OF TAX COMPLIANCE (A STUDY OF SME TAXPAYERS IN SIGI REGENCY) - Anatasya, Anatasya; Parwati, Ni Made Suwitri; Kahar, Abdul; Masruddin, Masruddin (Jurnal Manajemen Terapan dan Keuangan, 2026)
Tax compliance in the Small and Medium Enterprises (SME) sector presents a unique challenge in the era of tax digitalization in Indonesia. This study examines whether financial literacy and Coretax usage influence perceptions of tax compliance among culinary SMEs in Dolo District, Sigi Regency. Using a quantitative approach with multiple linear regression analysis, the research discovered that financial literacy takes a significant role in shaping positive perceptions of tax compliance. Similarly, Coretax usage has been shown to contribute to increased perceptions of compliance. However, these two factors only describe a small portion of the variation in tax compliance, indicating the presence of other external factors that need to be considered in further studies. The outcomes of this research are relevant for tax authorities in designing strategies to improve compliance by strengthening financial literacy capacity and optimizing digital tax systems, especially in regions with diverse geographic and economic characteristics. Kata kunci: Coretax, Tax Digitalization, Tax Compliance, Financial Literacy, SMEs